The Effect of Logo Care on Elderly’s Meaning of Life and Quality of Life in Werdha Nursing Home - Has, Eka Mishbahatul M; Vallentina, Tamara Regina; Hadisuyatmana, Setho (International Journal of Psychosocial Rehabilitation, 2020)
Logo care is a therapy to improve the meaning of life and quality of experience in the elderly. This study explains the effect of logo care on the meaning of life and quality of life in the elderly who live in a nursing home. This study used a quasi-experimental pretest-posttest with a control group design method. Sixty respondents were categorized into treatment groups and control groups randomly (single-blind). The independent variable is logo care, and the dependent variable is the meaning of life and quality of life. The research instrument used is the meaning of life questionnaire and the WHOQOL-BREF survey. Analysis using the Wilcoxon Signed Ranks Test and Mann Whitney test with a value of α=0.05. There are differences in the meaning of life and quality of life before and after logo care in the treatment group (p=0.001). There is a significant difference in the meaning of life (p=0.001) between the treatment group and the control group, also in the quality of life (p=0.001) between the treatment group and the control group. Logo care can increase the meaning of life and quality of life in the elderly with frequent counseling at the nursing home. By adding the frequency of logo care meetings, an optimal meaning and quality of life can be achieved.